Stripping of glidewire - A rare intraoperative complication of Percutaneous Nephrolithotomy - Sajad Ahmad para; Vipin kumar; Sajad Ahmad Wani (Urology Case Reports, 2022)
Percutaneous nephrolithotomy is the standard procedure used to treat nephrolithiasis. Glidewires play a pivotal role in the smooth conduction of the procedure. Rough handling of glidewires and other accessories can lead to their fragmentation or stripping thus complicating the procedure. These foreign bodies can get easily lost in the retroperitoneum and are difficult to retrieve. We present a case of stripping of glidewire during percutaneous nephrolithotomy and the procedure to retrieve it percutaneously under fluoroscopic guidance.